2020
DOI: 10.1177/0142331219900757
|View full text |Cite
|
Sign up to set email alerts
|

Event-triggered fault tolerant control for a class of state saturated systems subject to deception attacks

Abstract: This study is concerned with event-triggered fault tolerant control for a class of state-saturated systems subject to stochastic faults, unknown but bounded disturbances and deception attacks. After formulating stochastic faults, state saturations, and deception attacks, a hybrid system model is developed to facilitate analysis and design. An event-triggered transmission mechanism is proposed to decide whether the measurement values should be sent to the controller via wireless network. Since the sensor data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Moreover, we have shown that there is no Zeno behaviour exhibited. Our future research will focus on the nonlinear MASs under other types of attacks, such as deception attack (Gao et al, 2020) and false data-injection attack (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have shown that there is no Zeno behaviour exhibited. Our future research will focus on the nonlinear MASs under other types of attacks, such as deception attack (Gao et al, 2020) and false data-injection attack (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…By this scheme, the sampling and transmission of data is determined by a predefined performance dependent event-triggering condition and only necessary signals will be sent out. Event-triggered control has been investigated widely and many effective schemes are presented (Gao et al, 2020;Li et al, 2018;Qi et al, 2019aQi et al, , 2020bZhao et al, 2020). For example, a hybrid-triggering scheme which can be described by a Bernoulli variable is studied in Liu et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the control system may show a desirable performance many times without updating the control signal. This issue is very important in networked control systems (Gao et al, 2020;Shi et al, 2018), in which there is a network for communication between the sensors and actuators. Such a communication network (with a limited bandwidth) is shared between some system nodes.…”
Section: Introductionmentioning
confidence: 99%